2022
DOI: 10.11591/eei.v11i6.4269
|View full text |Cite
|
Sign up to set email alerts
|

A proposed approach for diabetes diagnosis using neuro-fuzzy technique

Abstract: Diabetes is a chronic disease characterized by a decrease in pancreatic insulin production. The immune system will be harmed due to this condition, which will raise blood sugar levels. However, early detection of diabetes enables patients to begin treatment on time, therefore reducing or eliminating the risk of severe consequences. One of the most significant challenges in the healthcare unit is disease diagnosis. Traditional techniques of disease diagnosis are manual and prone to inaccuracy. This paper propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Table 6 shows how our model with PID dataset outperforms all other existing models in terms of performance measures. The proposed model is evaluated against the most recent diabetes prediction models include (deep neural network [10], CART-GA, ANN-GA [8], Feedforward neural network [9], Artificial Neural Network+ Logistic Regression+DecisionTree [1], Random forest, J48 decision tree, Naïve Bayes, Naïve Bayes with feature selection three factors, and Naïve Bayes with feature selection five factors [25], DL, QML [13], DL [12], and ANFIS [14]). In terms of performance metrics, it showed that the suggested model performed better than these models.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 6 shows how our model with PID dataset outperforms all other existing models in terms of performance measures. The proposed model is evaluated against the most recent diabetes prediction models include (deep neural network [10], CART-GA, ANN-GA [8], Feedforward neural network [9], Artificial Neural Network+ Logistic Regression+DecisionTree [1], Random forest, J48 decision tree, Naïve Bayes, Naïve Bayes with feature selection three factors, and Naïve Bayes with feature selection five factors [25], DL, QML [13], DL [12], and ANFIS [14]). In terms of performance metrics, it showed that the suggested model performed better than these models.…”
Section: Resultsmentioning
confidence: 99%
“…The authors proved the DL techniques achieved high performance as compared with QML. Maher et al [14] suggest an approach to the diagnosis of diabetes relies on Adaptive Neuro-Fuzzy Inference System (ANFIS). This approach consists of several phases including, preprocessing phase, classification phase, and evaluation.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, another research article [11], [12], [13] analyzed the effectiveness of several machine learning models such as KNN, DT, RF, Naïve Bayes (NB), support vector machine (SVM), and logistic regression. The comparison of the performance of these machine-learning models reveals that the logistic regression model outperforms other models with an accuracy score of 75.32%.…”
Section: Introductionmentioning
confidence: 99%